2014
DOI: 10.1002/jib.127
|View full text |Cite
|
Sign up to set email alerts
|

Production of indigenous alcoholic beverages in a rural village of Tanzania

Abstract: In this study, the production techniques of indigenous alcoholic beverages in a rural village in Tanzania were investigated. In the village, three different kinds of alcoholic beverages were produced: a maize turbid beer (komoni), a straw beer (kimpumu) and a hybrid straw beer (kiambule). In the course of the production of these three alcoholic beverages, two different kinds of porridge, a fermented porridge (nyambo) as a source of yeasts and a sweet porridge (kikonde) as a source of saccharides, were produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…A similar brewing technique involving a mixture of two different types of porridge was also reported in southern Tanzania [14]. In that region, germinated finger millet is also used as an amylase source, and the brewing technique to control the temperature of the mixture during saccharification exists [14]. The results of this study showed that there were many brewing techniques shared between northeastern and southern Tanzania.…”
Section: Details Of the Brewing Technique Of Mbegesupporting
confidence: 57%
See 2 more Smart Citations
“…A similar brewing technique involving a mixture of two different types of porridge was also reported in southern Tanzania [14]. In that region, germinated finger millet is also used as an amylase source, and the brewing technique to control the temperature of the mixture during saccharification exists [14]. The results of this study showed that there were many brewing techniques shared between northeastern and southern Tanzania.…”
Section: Details Of the Brewing Technique Of Mbegesupporting
confidence: 57%
“…After 48 h of the fermentation, its ethanol concentration reached 4.0%, and its Brix value dropped to 6.0. A similar brewing technique involving a mixture of two different types of porridge was also reported in southern Tanzania [14]. In that region, germinated finger millet is also used as an amylase source, and the brewing technique to control the temperature of the mixture during saccharification exists [14].…”
Section: Details Of the Brewing Technique Of Mbegementioning
confidence: 91%
See 1 more Smart Citation
“…This surge in the English literature describes in detail the production of unique alcoholic beverages. Examples include advances in the production of innovative strains for sake production (Soejima et al 2012); the examination of ancient sake production techniques in Japan (Teramoto et al 2000); the rise in publications on studies of the indigenous flora in mud pit fermentations from China (Luo et al 2014;Huang et al 2014); and alcoholic products produced in Africa using traditional local ways (Kubo 2014 andKubo et al 2014). Many of these processes are all now being documented in detail in English in publications such as the 'Journal of the Institute of Brewing' published by the Institute of Brewing and Distilling.…”
Section: Global Beverage Alcohol Productionmentioning
confidence: 99%
“…Finally, an alcoholic beverage named mbege is produced with banana juice and finger millet in northern Tanzania . In addition to these alcoholic beverages, the author previously discovered an alcoholic beverage, named kimpumu , which was produced from finger millet in southern Tanzania . Taken together, the above facts show that finger millet is widely used for brewing in Eastern Africa.…”
Section: Introductionmentioning
confidence: 97%